Emergency contraceptive knowledge and associated factors among abortion experienced reproductive age women in Ethiopia: a multilevel analysis using EDHS 2016 data - Tadele Biresaw Belachew; Wubshet Debebe Negash; Daniel Gashaneh Belay; Fantu Mamo Aragaw; Melaku Hunie Asratie; Desale Bihonegn Asmamaw (BMC, 2023)
Abstract Background Emergency contraceptives (EC) are used to avoid unintended pregnancy, hence avoiding its incidence and its effects. In Ethiopia, emergency contraception is commonly accessible, especially in the big cities. However, there is virtually little understanding of or awareness of EC and Ethiopia has a high abortion rate. Therefore this study was aimed to assess the magnitude and associated factors for emergency contraceptive knowledge in Ethiopia. Methods The study was based on secondary data analysis of the Ethiopian Demographic and Health Survey 2016 data. A total weighted sample of 1236 reproductive age women was included. A multilevel mixed-effect binary logistic regression model was fitted to identify the significant associated factors of emergency contraceptive knowledge. Statistical significance was determined using Adjusted Odds Ratio (AOR) with 95% confidence interval. Results Overall magnitude of emergency contraceptive knowledge was observed to be 17.19% (95% CI: 15.18, 19.40) with intra-class correlation (ICC) 57% and median odds ratio (MOR) 6.4 in the null model. Women's age 25-34 (AOR = 2.6; 95% CI: 1.2, 5.5), and 35-49 (AOR = 1.5; 95% CI: 1.06, 3.3), secondary and above educational level (AOR = 3.41; 95% CI: 2.19, 4.88), media exposure (AOR = 2.97; 95% CI: 1.56, 5.64), Being in metropolitan region (AOR = 2.68; 95% CI: 1.46, 4.74), and women being in urban area (AOR = 3.19; 95% CI: 1.20, 5.23) were associated with emergency contraceptive knowledge. Conclusion Emergency contraceptive knowledge in this study was low. Women age, educational level, media exposure, residency, and region were significantly associated with emergency contraceptive knowledge. Therefore, to enhance understanding and use of ECs in the current Ethiopian setting, it is imperative to ensure exposure to EC information, particularly in rural regions.